POWER2GAS IN THE AUTOMOTIVE INDUSTRY - Best, Sabrina-Julia; Neubauer, Kevin; Timmerberg, Josef (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Because of the climate change and new laws to reduce the carbon dioxide emission, the automotive industry has a major potential. With alternative actuations and new ways to make fuels accessible, like Power2Gas, it is possible to drive nearly CO2 neutral. This examination considers especial passenger cars and lorries in Germany in terms of costs, different fuels and emission exhaust.